Analysis of changes in ecosystem capacity index and driving factors in the Loess Plateau under ecological engineering orientation - Yuan, Li; Zhong yuan, Mao; Bin, Xu; Yu xuan, Wan (Frontiers in Ecology and Evolution, 2024)
BackgroundIn recent decades, the Loess Plateau is one of the regions in China that urgently needs ecological governance due to the severe situation of soil erosion and land desertification. Due to the impact of climate change and human activities, the threat to the ecological space security of the Loess Plateau has intensified. This paper reveals the time lag effect of ecological engineering construction on the changes in the ecosystem service capacity index of the Loess Plateau, providing a scientific basis and decision-making reference for the sustainable development of the study area and improving the quality and management of ecological engineering construction, which is of great significance for building a solid ecological security barrier on the Loess Plateau.MethodsBased on the hierarchical analysis method, quantitative indicator method, spatial correlation analysis method and two-way fixed effect model, this paper analyzes the temporal and spatial changes of the ecosystem service capacity index of the Loess Plateau under the background of ecological engineering implementation.ResultsThe results showed that: 1) the vegetation coverage of the Loess Plateau increased with the increase of the area of ecological engineering construction, and showed a fluctuating growth distribution characteristic from southeast to northwest in space; 2) the water conservation capacity index, wind and sand fixation capacity index, biodiversity capacity index and comprehensive service capacity index of the Loess Plateau from 2000 to 2020 all showed exponential growth, which were highly coupled with the growth and change of vegetation coverage area in time and space; 3) the cold spots and hot spots of the ecosystem service capacity index of the Loess Plateau showed a step-by-step decrease of "hot in the south and cold in the north" in spatial distribution; the hot spots and sub-hot spots showed a reciprocating cycle from aggregation to fragmentation in time and space; the cold spots and sub-cold spots were mainly distributed in the northwest region. 4) The changes in the ecosystem service capacity index of the Loess Plateau were mainly affected by factors such as the cumulative project implementation area, urbanization rate and precipitation.ConclusionThe construction of ecological engineering on the Loess Plateau has achieved remarkable results. The growth of vegetation coverage area and ecosystem service capacity index on the Loess Plateau from 2000 to 2020 has promoted the recovery of ecosystem functions. Therefore, we should actively promote the construction of ecological projects to provide scientific decision-making references for solving regional ecological security issues.